Predictors of lateral lymph node metastasis and skip metastasis in patients with papillary thyroid microcarcinoma - Yoon, Jee Hee; Park, Ji Yong; Hong, A Ram; Kim, Hee Kyung; Kang, Ho-Cheol (Frontiers in Endocrinology, 2024)
Background: Papillary thyroid microcarcinoma (PTMC) is characterized by its favorable prognosis and potential for active surveillance (AS) as a management option. However, the presence of cervical lymph node (LN) metastasis, especially lateral LN metastasis, significantly impacts management and prognosis. Previous studies have focused on post-surgery risk factors for cervical LN metastasis. This study aims to identify predictors of lateral LN metastasis by analyzing pre-operative ultrasonographic findings alongside clinicopathological factors.Methods: A retrospective review of medical records was conducted for PTMC patients who underwent surgery at Chonnam National University Hwasun Hospital between 2004 and 2013. This is a case-control study that compares patients with lateral LN metastasis (N1b) to age and sex-matched patients without LN metastasis (N0). Subgroup analysis was performed to evaluate risk factors of skip metastasis.The study included 90 PTMC patients with lateral LN metastasis (N1b) and 268 age and sex-matched patients without LN metastasis (N0). The mean age was 49.3 years, and females were dominant in both groups. Structural recurrences of 4.4% (4/90) were observed only in the N1b group. The N1b group exhibited a higher frequency of upper lobe tumor location compared to the N0 group (38.9% vs. 16.0%, p<0.001). There was no significant difference in the locations with the presence of invasion to adjacent organs. A higher proportion of non-parallel shape was observed in the N1b group than the N0 group (80.0% vs. 66.0%, p=0.013). There were no differences in echogenicity, sonographic feature, margin, and AP diameter of the thyroid gland between the two groups. In multivariate analysis, independent risk factors for lateral LN metastasis included extrathyroidal extension, multiplicity, upper lobe tumor location, and non-parallel shape. Skip metastasis in PTMC patients was associated with upper lobe tumor location.Detailed ultrasound examinations, evaluating tumor location, number, orientation, and the presence of ETE, are crucial in accurately predicting lateral LN metastasis especially when primary tumor was in upper lobe to avoid missing skip metastasis. These evaluations can help guide the decision between active surveillance and immediate surgery in PTMC patients.